Problems of Systematization and Improvement of Legislation in the Sphere of Entrepreneurial Activity of Agriculture - Ruzinazarov Shukhrat Nuralievich (International Journal of Advanced Science and Technology, 2020)
This paper makes analyses of the problems of systematization and improvement of legislation in the sphere of entrepreneurial activity of agriculture. On this case, research has been pointed out from both theoretical and methodological basis.